Zarys sposobu funkcjonowania myśli ezoterycznej w kontekście polskim od XIX wieku do współczesności - Zaremba, Alicja (Wydział Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, Katedra Etnologii i Antropologii Kulturowej, 2018)
The purpose of the article is to show the ways of how esoteric is practisedand defined from XIXth century to the modern times, and how it shapes intovarious forms under cultural, economical, political and historical influences.The author compares different definitions and gives examples of how esotericis integrated in the Polish culture in miscellaneous ways, from affecting the market in the interwar period, through surviving the Polish People’s Republictime, to the rapid development, commercialisation and making of the esoterical industry in the posttransformational capitalism and the later changes it undergoes in the contemporary times.